Configuring NetScreen firewalls - Cameron, Rob (Syngress, 2005)
The first book on the market covering the #2 best-selling firewall appliances in the world from NetScreen. This book continues Syngress' history from ISA Server to Check Point to Cisco Pix of being first to market with best-selling firewall books for security professionals. Configuring NetScreen Firewalls is the first book to deliver an in-depth look at the NetScreen firewall product line. It covers all of the aspects of the NetScreen product line from the SOHO devices to the Enterprise NetScreen firewalls. Also covered are advanced troubleshooting techniques and the NetScreen Security Manager. This book offers novice users a complete opportunity to learn the NetScreen firewall appliance. Advanced users will find it a rich technical resource. * NetScreen is the #2 best-selling firewall appliance in the world (behind only Cisco PIX) and there are no competing books. * Covers the materials found on the NetScreen NCSA 5.0 exam. * Syngress firewall books are consistent best-sellers with market-leading books on ISA Server, Cisco PIX, and Check Point Next Generation.